Lease Accounting trouble looms for Corporate Real Estate Management. Issue 3 (19th August 2014) - Baltussen, Sjuul; Schelle, Tim; Appel-Meulenbroek, Rianne; van Egmond, Berend; Hesselink, Matthijs; van Leersum, Leon; Cooke, Howard
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose The purpose of this paper is to investigate what impact IFRS Lease Accounting changes might have on corporate real estate (CRE) strategies, and what the consequences for future corporate real estate portfolio decisions might be. Design/methodology/approach A macro analysis based on the constructive capitalization method of Imhoff, Lipe, and Wright (1991) is used to determine the potential impact of IFRS Lease Accounting changes on AEX listed corporations. In addition a series of interviews were held with CRE executives to discuss this impact and with CRE- and IFRS experts for general insight. Findings The impact of IFRS Lease Accounting seems less severe than expected. Notwithstanding, it could form a serious bottleneck for CRE departments that do not operate on a strategic level. Therefore, IFRS Lease Accounting changes might act as a catalyst for the professionalization of CREM departments. Practical implications The paper provides CRE managers with a manageable insight to alter CRE decision making processes in relation to IFRS Lease Accounting. The sample size was too small to make a distinction between different industries. Originality/value Past research showed that accounting is a potential variable in CRE decision-making, but did not yet clarify the possible impact of IFRS Lease Accounting on CRE strategies and the relating CRE operating decisions. Besides that, this paper also provides insight for options to cope with the (possibly severe) implications.